2008
DOI: 10.1016/j.bpc.2008.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity of natural and modified DNA measured by scanning tunneling microscopy. The effect of sequence, charge and stacking

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. A C C E P T E D M A N U S C R I P T ACCEPTED MANU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 35 publications
5
46
0
Order By: Relevance
“…Studying transport in thick molecular films and devices, such as organic thinfilm transistors or light-emitting diodes (Kratochvílová et al 2008). 2.…”
Section: Methods Of Characterization Of the Dna And Rna Electronic Prmentioning
confidence: 99%
See 4 more Smart Citations
“…Studying transport in thick molecular films and devices, such as organic thinfilm transistors or light-emitting diodes (Kratochvílová et al 2008). 2.…”
Section: Methods Of Characterization Of the Dna And Rna Electronic Prmentioning
confidence: 99%
“…The first electrical transport measurements of micrometer-long DNA ropes, followed by large numbers of DNA molecules, have indicated that DNA behaves as a good linear conductor (Porath et al 2000;Taniguchi and Kawai 2006). The Scanning Tunneling Microscope (STM) has already been proven (Kratochvílová et al 2008) as a very suitable tool for investigating ordered monolayer films, making it possible to contact one or more molecules and obtain images of the structural characteristics of the film. The experiments have also been used to investigate the room-temperature electronic properties of 12 base-pair d(GC) 12 -d (GC) 12 DNA molecules attached to the gold surface by a thiol link (Kratochvílová et al 2008).…”
Section: Oligonucleotides Between Two Electrical Contactsmentioning
confidence: 99%
See 3 more Smart Citations